2020
DOI: 10.1038/s41419-020-2730-7
|View full text |Cite
|
Sign up to set email alerts
|

Echinatin suppresses esophageal cancer tumor growth and invasion through inducing AKT/mTOR-dependent autophagy and apoptosis

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignant tumors with poor survival. It is urgent to search for new efficient drugs with good stability and safety for clinical therapy. This study aims to identify potential anticancer drugs from a compound library consisting of 429 natural products. Echinatin, a compound isolated from the Chinese herb Glycyrrhiza uralensis Fisch, was found to markedly induce apoptosis and inhibit proliferation and colony-formation ability in ESCC. Confocal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…Cholesterol metabolism has been proven to promote the survival and drug resistance of tumor cells to a certain extent ( Silvente-Poirot and Poirot, 2014 ; Yan et al, 2020 ). We have confirmed that the AKT/ERK pathway participates in the growth and metastasis of cancer cells in our previous studies, and this pathway has been proven to be the target of many anticancer drugs ( Xu et al, 2018 ; Hong et al, 2020 ; Xu et al, 2020 ; Hu et al, 2021 ). An increasing number of studies have confirmed that SREBP2 indeed plays a cancer-promoting role by regulating cholesterol metabolism in HCC ( Yang et al, 2019 ; Che et al, 2020 ; Liu et al, 2020 ), and SREBP2 has been proven to be the target of some anticancer drugs ( Kim et al, 2018 ; Kim et al, 2019 ).…”
Section: Introductionsupporting
confidence: 85%
“…Cholesterol metabolism has been proven to promote the survival and drug resistance of tumor cells to a certain extent ( Silvente-Poirot and Poirot, 2014 ; Yan et al, 2020 ). We have confirmed that the AKT/ERK pathway participates in the growth and metastasis of cancer cells in our previous studies, and this pathway has been proven to be the target of many anticancer drugs ( Xu et al, 2018 ; Hong et al, 2020 ; Xu et al, 2020 ; Hu et al, 2021 ). An increasing number of studies have confirmed that SREBP2 indeed plays a cancer-promoting role by regulating cholesterol metabolism in HCC ( Yang et al, 2019 ; Che et al, 2020 ; Liu et al, 2020 ), and SREBP2 has been proven to be the target of some anticancer drugs ( Kim et al, 2018 ; Kim et al, 2019 ).…”
Section: Introductionsupporting
confidence: 85%
“…Importantly, it has been reported that Ech can inhibit activation of the NF-ÎșB pathway 56 and the AKT/mTOR pathway. 57 Therefore, the protective effect of Ech may also involve other signal pathways, a hypothesis that needs further study. In addition, because the potential toxicity and side effects of Ech and its derivatives are still unclear, there is still a lot of research to be performed before this drug can be applied in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were executed as previously described 41 . CRC cells were exposed to varied concentrations of lomerizine 2HCl and fixed with methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were executed as previously described. 41 CRC cells were exposed to varied concentrations of lomerizine 2HCl and fixed with methanol. Then, after treating with 0.5% Triton X‐100, cells were blocked with 5% goat serum and treated with primary antibodies overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%